2012
DOI: 10.1002/jcu.21953
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of left chamber cardiac thrombi in patients with dilated left ventricle at sinus rhythm: The role of transesophageal echocardiography

Abstract: Dilation of left cardiac chambers offers a suitable terrain for thrombus formation. The high probability of LAA thrombosis should be kept in mind when designing the treatment strategy for patients with dilated cardiomyopathy at sinus rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 32 publications
(55 reference statements)
1
41
0
1
Order By: Relevance
“…An enlarged LA could be a predictive factor for the occurrence of stroke [26]. A previous study has shown that LA volume was correlated with LAA maximal area, which was an independent predictor for LAA thrombus formation [27]. In the present study, the maximum LA volume (LAVmax) was found to be an independent risk factor for LAAT even after adjusting for other factors such as aging and hypertension.…”
Section: Maximal Left Atrial Volume and The Risk Of Laa Thrombussupporting
confidence: 49%
“…An enlarged LA could be a predictive factor for the occurrence of stroke [26]. A previous study has shown that LA volume was correlated with LAA maximal area, which was an independent predictor for LAA thrombus formation [27]. In the present study, the maximum LA volume (LAVmax) was found to be an independent risk factor for LAAT even after adjusting for other factors such as aging and hypertension.…”
Section: Maximal Left Atrial Volume and The Risk Of Laa Thrombussupporting
confidence: 49%
“…More infrequently formation of left ventricular thrombus occurs in patients with myocardial infarction,12 dilated cardiomyopathy1 and acute myocarditis 13…”
Section: Discussionmentioning
confidence: 99%
“…Studies estimate left ventricular thrombus to occur in 13% of patients with dilated cardiomyopathy during sinus rhythm 1. According to guidelines, patients with atrial fibrillation should be treated with anticoagulation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Dilated cardiomyopathy favours the formation of intracardiac thrombi, a potential source of embolism. The examination of 45 patients with dilated cardiomyopathy with mild to moderate systolic dysfunction, who were at sinus rhythm and without anticoagulation therapy, revealed left ventricular thrombus in 13.3% and left atrial appendage thrombus in 68.9% [12]. Factors that predispose to thromboembolic events in patients with congestive heart failure (CHF) include low cardiac output, with relative stasis of blood in dilated cardiac chambers, poor contractility, and regional wall motion abnormalities [13].…”
Section: Streszczeniementioning
confidence: 99%